Genomic and Pathological Characterization of Multiple Renal Cell Carcinoma Regions in Patient With Tuberous Sclerosis Complex: A Case Report - Yamamoto, Tetsuya; Kato, Taigo; Hatano, Koji; Kawashima, Atsunari; Ujike, Takeshi; Fukuhara, Shinichiro; Kiuchi, Hiroshi; Imamura, Ryoichi; Ibuki, Naokazu; Kiyotani, Kazuma; Kurashige, Masako; Morii, Eichi; et al. (Frontiers in Oncology, 2021)
Tuberous sclerosis complex is a genetic disorder characterized by facial angiofibromas, intellectual disability, epilepsy, and tumor formation in multiple organs, including the kidney. Renal cell carcinoma occurs in 2%–4% of patients with tuberous sclerosis complex, often developing multiply and bilaterally. Renal cell carcinoma associated with this genetic disorder may include complex tumor heterogeneity caused by the spatially different mutational landscape. Herein, we report the case of a female patient with tuberous sclerosis complex who developed multiple renal tumors. A 44-year-old female patient with tuberous sclerosis complex developed three different histological types of tumor—angiomyolipoma, clear cell renal cell carcinoma, and papillary renal cell carcinoma—in the left kidney at first renal cell carcinoma recurrence. The papillary renal cell carcinoma was morphologically atypical, indicating that its occurrence was associated with the genetic disorder. Furthermore, whole-exome sequencing revealed distinct patterns of somatic mutation in the three tumor types, and the atypical papillary renal cell carcinoma possessed a different mutational landscape than that of typical papillary renal cell carcinomas. Our findings indicate that tumors associated with tuberous sclerosis complex may be diagnosed with careful pathological examination. Furthermore, somatic mutation profiles of these tumors revealed their unique features, providing important information for further understanding the mechanism of multiple tumor development in patients with tuberous sclerosis complex.